THE DEPICTION OF THE ROMANIAN COMMUNITY'S UNHEARD VOICES IN I MUST BETRAY YOU: SUBALTERN ANALYSIS - Umi Trinatasya; Darmawan , Ruly Indra (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2024)
This subaltern study addresses the abuse of power that oppresses the subaltern. In the novel history fiction, I Must Betray You (2022) by Ruta Sepetys. This article analysis uses Gayatri Chakravorty Spivak's subaltern approach based on her essay “Can the Subaltern Speak